FAKTOR INTERNAL DAN PERSEPSI IBU TENTANG PERAN PETUGAS KESEHATAN TERHADAP PEMBERIAN ASI EKSKLUSIF - Hinisa, Fariha Nuzulul; Wardani, Diadjeng Setya; Andarini, Sri; Simanjuntak, Roganda (Media Penelitian dan Pengembangan Kesehatan, 2024)
During the first 6 month period, newborns who are exclusively breastfed consume solely breast milk and abstain from any other form of nourishment, such as food or liquids, including water. The government Indonesia has pledged to attain a target proportion of exclusive breastfeeding, with a goal of reaching up to 80%. The X Community Health Centre in Malang City achieved a relatively low level of exclusive breastfeeding coverage in 2022, with only 51.18%. This falls far short of the established target. Internal variables and the mother's opinion of the involvement of health personnel are influential in determining exclusive breastfeeding. The aims of this research were to analyses the influence of internal factors and maternal perspectives on the role of healthcare providers in promoting exclusive breastfeeding. This cross-sectional study was conducted in January-March 2024 at the X Health Centre Working Area in Malang City. The study utilized observational analytics. The study's sample consisted of one hundred moms with children older than six months. Chi-square test yields identify there wasn't significant association between employment also having multiple children (p-value>0.05). However, various factors related to exclusive breastfeeding, like as age, education, family support, and mother's intellectual and perception about the role of health workers, were found to be significantly associated (p-value <0.05). The multivariate analysis using multiple logistic regression revealed that family support has a significant impact on exclusive breastfeeding. The p-value of 0.006 and an odds ratio of 26,595 indicate that family support increased the likelihood of exclusive breastfeeding by 26-fold.